2011
DOI: 10.1159/000324432
|View full text |Cite
|
Sign up to set email alerts
|

Basics of Systematic Reviews and Meta-Analyses for the Nephrologist

Abstract: Renal practitioners are expected to apply the best available evidence from rigorous scientific research to clinical decision-making and also for policy-making for those involved. Advances in information technology and unprecedented access to data have simplified the process for the search of best available evidence to guide practice. However, it is challenging to cope with the increasing volume of publications in nephrology and other areas of medicine. Accordingly, systematic reviews and meta-analysis have gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 122 publications
0
1
0
1
Order By: Relevance
“…Lobo et al showed that zinc is negatively associated with lipid peroxidation (LDL) and inflammatory markers like TNF alpha (TNF-alpha) and CRP, which were independently associated with CV mortality. 35 However, zinc deficiency was not found to be associated with higher risks of clinical outcomes including all-cause death, CV events, and infections in a study by Tonelli et al 38…”
Section: Changes In Zinc Homeostasis In Ckd/esrdmentioning
confidence: 97%
“…Lobo et al showed that zinc is negatively associated with lipid peroxidation (LDL) and inflammatory markers like TNF alpha (TNF-alpha) and CRP, which were independently associated with CV mortality. 35 However, zinc deficiency was not found to be associated with higher risks of clinical outcomes including all-cause death, CV events, and infections in a study by Tonelli et al 38…”
Section: Changes In Zinc Homeostasis In Ckd/esrdmentioning
confidence: 97%
“…Od ukupnog broja publiciranih studija do 2008. godine svega 10 % randomiziranih kliničkih studija je bilo sažeto u sustavnim preglednim člancima (1.000 od dotad postojećih 10.000 randomiziranih kliničkih studija) 9 . No, da bi publicirane studije bile bliske prosječnom čitatelju -nefrologu, kao i sustavni pregledni članci, publicirano je nekoliko članaka koji se bave tematikom kako kritički sagledati kliničke studije u nefrologiji, što tražiti u metaanalizama te kako koristiti sustavne pregledne članke [16][17][18] .…”
Section: Cochrane U Nefrologijiunclassified